Public Administration in Ethiopia Case Studies and Lessons for Sustainable Development - Debela, Bacha Kebede; Bouckaert, Geert; Warota, Meheret Ayenew; Gemechu, Dereje Terefe (Leuven University Press, 2020)
First handbook on Ethiopian Public AdministrationBuilding an effective, inclusive, and accountable public administration has become a major point of attention for policymakers and academics in Ethiopia who want to realise sustainable development. This first handbook on Ethiopian Public Administration is written by Ethiopian academics and practitioner-academics and builds on PhD studies and conference papers, including studies presented at the meetings of the Ethiopian Public Administration Association (EPAA), established in 2016.Public Administration in Ethiopia presents a wide range of timely issues in four thematic parts: Governance, Human Resources, Performance and Quality, and Governance of Policies. Each of the individual chapters in this volume contributes in a different way to the overarching research questions: How can we describe and explain the contexts, the processes and the results of the post-1990 politico-administrative reforms in Ethiopia? And what are the implications for sustainable development?This book is essential for students, practitioners, and theorists interested in public administration, public policy, and sustainable development. Moreover, the volume is a valuable stepping stone for PA teaching and PA research in Ethiopia.Contributors: Adare Assefa Mitiku (Defense Construction Enterprise), Aklilu Wubet Lema (Addis Ababa University), Alebachew Asfaw Yimer (Bahir Dar University), Annie Hondeghem (KU Leuven), Bacha Kebede Debela (Ambo University), Bahiru Deti Heyi (Dilla University), Belayneh Bogale Zewdie (Kotebe Metropolitan University), Geert Bouckaert (KU Leuven), Gutata Goshu Amante (Addis Ababa University), Bruno Broucker (KU Leuven), Challa Amdissa Jiru (Addis Ababa University), Defferew Kebebe Tessema (Addis Ababa University), Denamo Addissie Nuramo (Addis Ababa University), Deribe Assefa Aga (Ethiopian Civil Service University), Dessalegn Kebede Kedida (Oromia Police College), Frehiwot Gebrehiwot Araya (Addis Ababa City Public Service and Human Resource Development Bureau), Henok Seyoum Assefa (Ethiopian Public Administration Association, EPAA), Hirko Wakgari Amanta (Oromia State University), Hiwot Amare Tadesse (Ambo University), Kassa Teshager Alemu (Ethiopian Civil Service University), Kiflie Worku Angaw (Dilla University),Moti Mosisa Gutema (Dilla University), Solomon Gebreyohans Gebru (KU Leuven), Steve Troupin (KU Leuven), Temesgen Genie Chekol (Dire Dawa Institute of Technology), Tewelde Mezgobo Ghrmay (Mekelle University), Trui Steen (KU Leuven), Meuriaw Ayalew (Assosa University / Addis Ababa University), Zekarias Minota Seiko (Ethiopian Civil Service University / Addis Ababa University)